Impact of the Encapsulation Process by Spray- and Freeze-Drying on the Properties and Composition of Powders Obtained from Cold-Pressed Seed Oils with Various Unsaturated Fatty Acids - Dorota Ogrodowska; Małgorzata Tańska; Waldemar Brandt; Sylwester Czaplicki (Polish Journal of Food and Nutrition Sciences)
The aim of this study was to determine the influence of encapsulation methods on fatty acid composition and content of bioactive compounds in cold-pressed oils. Rape, flax, and safflower seed oils (10.2%) were mixed with water (70.0%) and wall components (19.8%) to obtain emulsions, which were then subjected to spray- and freeze-drying. Surface and total oil contents, and changes in contents of fatty acids, sterols, and tocopherols were compared in powders and natural oils. The spray-drying was a more effective encapsulation method compared to the freeze-drying. Fatty acid composition of the oils was quite stable during the encapsulation process. Sterol degradation was high and only 35-40% of these compounds were determined in powders. In turn, tocopherol losses were dependent both on the encapsulation method and oil type. The encapsulation by freeze-drying allowed the retention of almost all tocopherols of cold-pressed flax and safflower seed oils.